Making Sense : the Child's Construction of the World. - Bruner, Jerome S. (Routledge revivals., 2011)
The growing child comes to understand the world, makes sense of experience and becomes a competent social individual. First published in 1978, "Making Sense" reflected the way in which developmental psychologists had begun to look at these processes in increasingly naturalistic, social situations. Rather than seeing the child as working in isolation, the authors of this collection take the view that 'making sense' involves social interaction and problem-solving. They particularly emphasize the role of language; its study both reveals the child's grasp of the frames of meaning in a pa.